Self-Phase Modulation Effect on Performance of 40 Gbit/s Optical Duty-Cycle Division Multiplexing Technique - Mahdiraji, Ghafour Amouzad; Abas, Ahmad Fauzi (De Gruyter, 2012)
Self-phase modulation (SPM) effect on performance of 40 Gbit=s (3 x 13.33 Gbit=s) optical duty-cycle division multiplexing (O-DCDM) over 400 km (5 x 80 km) standard single mode fiber (SSMF) based on three different dispersion compensation schemes is investigated by simulation. The result shows that the SPM effect is very strong in dispersion pre-compensation compared to postcompensation. Further reduction in SPM effect is observed by combination of pre- and post-compensation with the optimum pre-compensation value of around 215 ps=nm. The simulation is performed at different launched power into dispersion compensation fiber (DCF). The range between -6 to -8 dBm is observed as the optimum power for all dispersion compensation schemes. The highest SPM threshold is observed when dispersion pre- and post-compensation are used together, which is around C6:7 dBm. In addition, the optimum range of launched power into SSMF for different transmission distances from 80 km to 1280 km is also presented.